Transition from school to adult life for physically disabled young people. Issue 4 (1st October 1998) - Fiorentino, L; Datta, D; Gentle, S; Hall, D M B; Harpin, V; Phillips, D; Walker, A
Abstract : The transition process for young physically disabled people (n = 87) was studied in three districts to determine how it varied between schools, and how it was perceived by the disabled and their carers. The experiences of the young people were compared with guidelines for good practice based on relevant legislation. Results showed that young disabled people experienced a poor handover to adult services if they had no "statement of special educational need" or if they went to further education college. Young people with cerebral palsy or complex multiple problems fared less well than those with spina bifida or juvenile chronic arthritis. There are several deficiencies in the legislation. Physically disabled young people should receive a transition review regardless of whether they have a "statement". The range of severity and type of disorders among the young physically disabled argues for a range of services—the category is too broad to be useful for research, service planning, and provision.